EVALUASI EFEKTIVITAS PELAKSANAAN PENAGIHAN PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA KABANJAHE - Hotmaida Naibaho; Duma Rahel Situmorang (JURNAL MANAJEMEN, 2018)
In increasing state revenues in the tax sector, the Ministry of Finance of the Republic of Indonesia in this case the Directorate General of Taxes continues to strive to carry out tax collection on taxpayers who have not paid their tax debt. This study aims to determine the effectiveness of the implementation of tax collection, knowing the efforts that have been made by the KPP Pratama Kabanjahe, as well as the obstacles faced in order to increase the disbursement of tax arrears. The analysis technique used is a descriptive analysis method, namely the analysis carried out by collecting the actual data, presenting and analyzing the data so that information can give a clear picture of the object under study and then draw a conclusion, besides the descriptive method the author also uses effectiveness ratio, library method and documentation from the KPP Pratama Kabanjahe. Data analysis method that explains the determination of the effectiveness of the implementation of tax collection based on the Circular of the Director General of Taxes concerning Tax Collection Policy, by looking at the development of tax collection from the effectiveness of the target of disbursement of tax arrears and evaluating the performance of active collection of tax bills through evaluation of letters of reprimand, evaluation of forced letters, evaluation of warrant foreclosure, evaluation on auction orders. The results showed that the determination of the achievement level of KPP Pratama Kabanjahe tax arrears for 2014 based on the effectiveness indicators could be concluded to be quite effective, whereas for 2015 and 2016 it was concluded that it was not effective.